Réponses

2014-09-21T17:14:58+02:00


A = 5 + 8 x (-2) + 6

A = 5 + (-16) + 6

A = -11 + 6

A = -5


B = 4 - 7 x (-3 + 8)

B = 4 - 7 x 5

B = 4 - 35

B = - 31


C = (3 - 7) x (5 + 2)

C = - 4 x 7

C = - 28


D = (-3 - 6 ) x (6 - 8)

D = - 9 x - 2

D = 18


E = 5 - (2 x 7 - 13)

E = 5 - (14 - 13)

E = 5 - 1

E = 4


F = 30 - (7 - 2 x 8)

F = 30 - (7 - 16)

F = 30 - (-9)

F = 30 + 9

F = 39


G = (6 x 5 - 3) x (7 - 2 x 6)

G = (30 - 3) x (7 - 12)

G = 27 x (- 5)

G = -135


H = (9 : 3 + 5) x (7 x (-4) + 2)

H = (3 + 5) x (-28 + 2)

H = 8 x (- 26)

H = -208


I = 40 - [ 28 - ( 3 x 2 + 4)]

I = 40 - [ 28 - (6 + 4)]

I = 40 - [ 28 -10 ]

I = 40 - 38

I = 2


J = [ 30 - (2 + 8 x 3)] - [ 50 - (12 - 2 x 5)]

J = [ 30 - (2 + 24)] - [ 50 - (12 - 10)]

J = [ 30 - 26 ] - [ 50 - 2 ]

J = 4 - 48

J = - 44